Book Review of Breathe, Freedom: A Comprehensive and Hypnotic Approach to Quitting Smoking (Canadian Journal of Counselling and Psychotherapy, 2012)
This book review focuses on the story of Freedom who, in his quest for belonging, becomes addicted to cigarettes. Through living hard and being forced to learn life’s lessons, Freedom becomes enlightened and overcomes his addiction through medical and psychosocial interventions. The narrative serves as a backdrop to presenting a multicomponent treatment program. The program includes smoking cessation aids, drug therapy approaches, and hypnosis to help the reader achieve abstinence after one year at a purported success rate of 50%. The author reassures us that this is evidence of efficacy, given that smoking is an addiction and not just a habit.